Gambaran Perilaku Ramah Lingkungan Mahasiswa Binus Ditinjau dari Tingkat Kesadaran Lingkungan - Murty Magda Pane (Bina Nusantara University, 2013)
Environmental quality of Jakarta has further experienced decline. It is time for the society of Jakarta has higher environmental awareness, reflected from the frequent of friendly environmental behavior implemented. To intervene so that people behave environmentally friendly is certainly not easy, but the intervention can begin by getting an overview for environmental behavior of the society. This intervention can be initiated from public intellectuals. Binus students, as young intellectuals considering as one of the largest population in Jakarta, have great potentials in initiating interventions that lead to the formation of urban eco-friendly behavior to determine Jakarta. As the appropriate intervention, it requires initial overview of environmental behavior of Binus students. Hence this study took students in second semester as respondents. The objective of this study is to get the illustration of the level of environmental awareness of the students. Afterwards it is expected to be the basis for further research to determine appropriate interventions. This study used quantitative method to determine the level of environmental awareness of the respondent. While the results showed that the respondents' level of environmental awareness is still below the expectancy level.